The usage of cybernetic in complex software systems and its application to the deterministic multithreading - Bozkurt, Erkam Murat (Concurrency and computation, 2022)
Abtract In this paper, a new cybernetic control technology that can be used in complex software systems will be introduced. In this approach, the software systems are governed by cybernetic control objects and the class libraries defining the types of these cybernetic control objects are produced by special meta‐programming platforms. In this approach, the requirements of the software to be developed are received from the programmer by meta‐programming systems before coding. Actually, the cybernetic control objects have standard design and properties and the programmers only determine the quantities and the locations of these properties before library production process. Then, the meta‐programming platforms build project‐specific class libraries based on previously determined code templates. By this way, the cybernetic control objects are constructed with optimal memory and they can receive feedback about ongoing operations on the process. With the help of the feedback coming from the process, the control objects steer the process in the line of the programmer directives. By this way, the control of the programmer on the software increases significantly. In addition, in this paper, a typical application of this approach to the multithread programming will be introduced.